Beekeeping after War - Leach, Tomas (Italy, 2006)
Verzio FF submission A documentary about the former Yugoslavia, as told by the beekeepers of the land. The war-scarred lands of the former Yugoslavia are home to a great history of Beekeepers. These men and women are woven into the culture and narrative of the bitter past of this beautiful and scarred terrain. Their stories are that of the Balkans. They have seen some of the bitterest fighting in World War 2. They have lived forcibly united under Communism and they have suffered under the NATO sanctions and bombing. All the while, they have produced outstanding honey. Beekeepers from across the land tell us their stories, patiently, passionately. Sister Nektarina, an orthodox nun talks of how bees have always been part of monastery life. The Ba_i_ Brothers bemoan the quality of honey now that they can no longer move their hives freely from pasture to pasture. 22 year-old Marko wishes that the authorities would see the good that beekeepers do and help them build the economy.